CLINICAL CHARACTERISTICS OF NON-DEPOLARIZING MUSCLE RELAXANTS AS A COMPONENT OF GENERAL ANESTHESIA DURING PROLONGED ELECTIVE SURGERY - Шкурупій, Д.А.; Похилько, В.І. (World of Medicine and Biology, 2014)
Іn the article is presented сomparative description of clinical effects of non-depolarizes muscle relaxants – pipecuronium bromide and atracurium besylate during the planned operative interferences. It is marked, that a pipecuronium bromide creates terms to forming of intraoperative hypotension, and atracurium besylate – to forming of postoperative hypotension. In same time, muscle relaxation with the use of atracurium besylate, by comparison to application of pipecuronium bromide, creates the terms of more comforts for tracheal intubation, is relaxation and time of action more guided on a level.
Keywords: surgical operations; non-depolarizes muscle relaxants